Treatment analysis of gas gangrene in the "Hospital de Clínicas" - Asiner, Boris (Cirugía del Uruguay, 1972)
We have collected 14 observations of gas gangrene assisted in our Hospital University, corresponding to a period of 15 years. His recognition was clinical, with bacteriological verification -clostridium welchii, perfringens- positive in 11 cases.